Characterization and differentiation of CD51+ Stem Leydig cells in adult mouse testes. (1st August 2019) - Chen, Panpan; Guan, Xiaoju; Zhao, Xingxing; Chen, Fenfen; Yang, Jianying; Wang, Yiyan; Hu, Yue; Lian, Qingquan; Chen, Haolin
Abstract: It was reported previously that adult mouse stem Leydig cells (SLCs) express CD51 (integrin α-chain V). However, it is still unclear whether all CD51 +  cells are SLCs. In the present study, we found that CD51 +  cells can be classified into two sub-groups, a weakly-staining group (CD51 + ) and a strongly-staining group (CD51 ++ ). The CD51 +  cells expressed common SLC marker genes, including Nestin, Pdgfra and Coup-tf2, while CD51 ++ cells did not express these genes. Instead, they expressed macrophage markers, such as F4/80, Cd115 and Tnfa. When these cells were induced to differentiate in vitro, the CD51 +  cells, but not CD51 ++ cells, formed Leydig cells. Overall, our results showed that although SLCs expressed CD51, not all CD51-expressing cells are SLCs. The cells that expressed high levels of CD51 are actually macrophages. Highlights: CD51 +  cells of adult mouse testes contain two sub-populations. The weakly-positive CD51 expressing cells in adult mouse testes are stem Leydig cells. The strongly-positive CD51 cells in adult mouse testes are macrophages.